Hypospadias and Increased Risk for Psychiatric Symptoms in Both Childhood and Adolescence: A Literature Review - Jin, Tingting; Wu, Weizhou; Shen, Maolei; Feng, Haiya; Wang, Ya; Liu, Shixiong; Li, Xin; Zhao, Shankun (Frontiers in Psychiatry, 2022)
Hypospadias is one of the most common congenital malformations in boys. Due to abnormal appearance in the penis with abnormal urination and erection, patients with hypospadias were vulnerable to suffering from stress and psychiatric difficulties. The present study aims to summarize all the current evidence of the association between hypospadias and the risk of psychiatric disorders by a comprehensive review. Seventeen clinical studies were identified in the four electronic databases. A total of 953,872 participants were involved, while 15,729 of them were hypospadiac patients and the remaining 938,143 were normal controls. The standard age for surgery for hypospadias ranged from 20.4 months to 21.5 years. Eight out of seventeen (8/17, 47%) included studies explicitly showed that patients with hypospadias had a significantly higher risk of psychosocial disorders (all P < 0.05). Specific types of psychiatric disorders included depression, anxiety, shyness, timidness, isolation, fear of ridicule, attention-deficit hyperactivity, autism spectrum, behavioral/emotional disorders, temper tantrums, emotionality, affective, psychosexual problems, and suicidal tendencies. Based on this review, psychiatric illnesses are frequently detected in hypospadiac patients' childhood, thus proper psychiatric guidance and early interventions from physicians, nurses, and parents may help these children to grow into less affected men.